1993
DOI: 10.1111/j.1365-2761.1993.tb00868.x
|View full text |Cite
|
Sign up to set email alerts
|

Leucocytes from Atlantic salmon, Salmo salar L., experimentally infected with infectious salmon anaemia (ISA) exhibit an impaired response to mitogens

Abstract: The proliferative response to mitogens of head kidney leueoeytes from Atlantic salmon, Salmo salar L., experimentally infected with infectious salmon anaemia (ISA) was examined. The mean hacmatocrits of ISA-inoculated fish were significantly lower than the mean haematocrits of eontrol-inoculated fish at day 14. Mortality in ISA-inoculated fish appeared at day 16 after inoculation. Seven days after inoculation, leucocytes from ISA-inoculated fish showed an increased response to phytohaemagglutinin (PHA) compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 10 publications
4
22
0
Order By: Relevance
“…infection with isolate 0390/98, in support of previous studies using both Norwegian (Dannevig et al 1993, Totland et al 1996 and Canadian isolates (Jones et al 1999, Lovely et al 1999. Thus, the absence of disease in freshwater salmon farms is likely to be due to insufficient infectious pressure at these farms.…”
Section: Discussionsupporting
confidence: 84%
“…infection with isolate 0390/98, in support of previous studies using both Norwegian (Dannevig et al 1993, Totland et al 1996 and Canadian isolates (Jones et al 1999, Lovely et al 1999. Thus, the absence of disease in freshwater salmon farms is likely to be due to insufficient infectious pressure at these farms.…”
Section: Discussionsupporting
confidence: 84%
“…While the physical relationship between ISAV particles in blood and the circulating erythrocytes is not known, it is clear from our study that ISAV does not replicate in circulating red blood cells. This is consistent with data cited by Dannevig et al (1993) which showed that in vitro inoculation of salmon erythrocytes or reticulocytes with infective ISA material did not result in ISAinfective cells as judged by transmission trials in fish.…”
Section: Resultssupporting
confidence: 92%
“…While the physical relationship between ISAV particles in blood and the circulating erythrocytes is not known, it is clear from our study that ISAV does not replicate in circulating red blood cells. This is consistent with data cited by Dannevig et al (1993) which showed that in vitro inoculation of salmon erythrocytes or reticulocytes with infective ISA material did not result in ISAinfective cells as judged by transmission trials in fish.In conclusion, this study demonstrates that viremia in ISAV infection is associated with virus replication in leucocytes, and that erythrocytes are not target cells for virus replication. Studies are in progress to establish the physical relationship (if any) between ISAV particles in blood and the circulating erythrocytes in ISAV-infected fish.…”
supporting
confidence: 92%
“…Atlantic salmon presmolts with an average weight of about 100 g were obtained from a salmon hatchery where ISA had never been diagnosed. Each of 200 fish was injected intraperitoneally with 0.5 m1 ISAV-infective tissue homogenate prepared from experimentally infected salmon, as described elsewhere (Dannevig et al 1993). The fish were kept at 12°C in fresh water in a 1 m* tank.…”
Section: Methodsmentioning
confidence: 99%